Sex Differences in the Nicotinic Acetylcholine Receptor System of Rodents: Impacts on Nicotine and Alcohol Reward Behaviors - Moen, Janna K.; Lee, Anna M. (Frontiers in Neuroscience, 2021)
Alcohol and nicotine are the two most widely used and misused drugs around the world, and co-consumption of both substances is highly prevalent. Multiple lines of evidence show a profound effect of sex in many aspects of alcohol and nicotine reward, with women having more difficulty quitting smoking and showing a faster progression toward developing alcohol use disorder compared with men. Both alcohol and nicotine require neuronal nicotinic acetylcholine receptors (nAChRs) to elicit rewarding effects within the mesolimbic system, representing a shared molecular pathway that likely contributes to the frequent comorbidity of alcohol and nicotine dependence. However, the majority of preclinical studies on the mechanisms of alcohol and nicotine reward behaviors utilize only male rodents, and thus our understanding of alcohol and nicotine neuropharmacology relies heavily on male data. As preclinical research informs the development and refinement of therapies to help patients reduce drug consumption, it is critical to understand the way biological sex and sex hormones influence the rewarding properties of alcohol and nicotine. In this review, we summarize what is known about sex differences in rodent models of alcohol and nicotine reward behaviors with a focus on neuronal nAChRs, highlighting exciting areas for future research. Additionally, we discuss the way circulating sex hormones may interact with neuronal nAChRs to influence reward-related behavior.